Bible mysteries solving the Bible's greatest mysteries - Bragard, Jean-Claude; Cox, Anna (BBC Worldwide Limited, 2004)
Bible mysteries explores great figures and events from biblical times. Historical, archeological and anthropological evidence gives fresh insights into the historical realities of the times.